Using a video presentation on variance and covariance in the teaching of statistics. (21st December 2021) - Austerschmidt, Kim L.; Stappert, Alexander; Heusel, Hanna; Bebermeier, Sarah
Abstract: We outline the use and evaluation of a video presentation about variance and covariance developed to motivate students to process the topics and to enhance their skills. We outline the structure and the content of the video presentation and present data of an evaluation study. Students in different subjects who must pass statistics courses (N = 114) participated in an online survey with randomized controlled design and repeated measurement. Results indicate that students who watched the video presentation significantly improved on their skills, compared to a control group reading a textbook section about the same topics. The video presentation was judged as more satisfying and useful for learning than the text. We discuss application scenarios and further teaching implications. Ideally a longitudinal study should investigate effects of continuous learning with video presentations, changes in motivation, anxiety, and attitudes as well as effects for students of different subjects.